How chronic ear disease affects quality of life: a qualitative research study in Nepal. Issue 4 (29th April 2022) - de Cates, C; Jashek-Ahmed, F; Bohara, RB; Salter, C; Youngs, R
Abstract: Objective: Hearing loss is the third leading cause globally for 'years lived with disability'. The majority of those affected live in low and middle-income countries. Method: This study used qualitative research methods to explore the impact of chronic ear disease on quality of life in Nepal. Twenty face-to-face semi-structured interviews were conducted during a visiting ear camp at the Britain Nepal Otology Service Ear Care Centre in Nepal. Interviews were recorded, transcribed and translated with thematic content analysis performed manually by two researchers. Results: Chronic ear disease has a significant impact on social interactions, emotional well-being and functionality. Barriers to surgery are cost, accessibility, reputation, gender and fear of complications. Conclusion: This study provided valuable new insight into patient perspectives on living with chronic ear disease in Nepal. Patients with chronic ear disease experience discrimination and stigmatisation across all levels of personal, family and social life, with their function across all domains being directly limited by symptoms.